Attitudes of health workers and outpatients’ recovery in public hospitals in Calabar Metropolis, Nigeria: An Information Analysis - Agba, A. M. Ogaboh; Ojong, Felix E.; Akintola, Abayomi I.; Maruf, Gbadebo S.; Udom, Hannah T.; Usung, Essienawan U. (JINAV: Journal of Information and Visualization, 2021)
The study is an information analysis about the assessed awareness of the attitudes of health workers and outpatients’ recovery in public hospitals in Nigeria. Specifically, the study examined negligence and aggressive behaviour by health workers on outpatients’ recovery in public hospitals. The study was carried out in public hospitals in Calabar Metropolis, Nigeria. The cross-sectional design method was adopted to collect empirical data from outpatient in the hospitals for three months. The study adopted the purposive and volunteer sampling techniques in identifying 400 respondents for the study. Data collected were analysed using simple percentages and Chi-squared statistical tools. Results revealed that there is significant relationship between negligence by health workers and outpatients’ recovery (χ2 = 13.45 ≥ 7.815), health workers’ aggression significantly affect outpatients’ recovery (χ2 = 97.09 ≥ 7.815). Based on these findings, it was recommended among others that management of public hospitals should put on measures to curtail attitudes of negligence by staff towards patients, by installing closed-circuit television (CCTV) cameras specifically along service points. Management of public hospitals should impose stiff and stringent penalties on staff found to be aggressive towards patients.